Bingkai Media terhadap Hubungan Bilateral Indonesia-Malaysia (Analisis Framing Terhadap Pemberitaan Sengketa Perbatasan Kelautan dan Perairan Indonesia-Malaysia Pasca Insiden 13 Agustus 2010 dalam Kompas online) - Gatut Priyowidodo; Inri Inggrit Indrayani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
The relations between Indonesia and Malaysia are always full of colors. Indonesia and Malaysia are assumed as neighbour since it has similar history, religion also socio culturally. Some decades show that the decline of relationship the both countries. Another time, as ASEAN members the two countries devotes their nationalities to purify their collective identities as Eastern. The objective of the research is to extricate the construction of Kompas online toward news coverage of the borders dispute between Indonesia-Malaysia in 2010. This research is proposed to examine central issues which reported by Kompas online consistently. As a media industry, Kompas coverage dominates circulation nationally. Kompas was the pioneer of online news in Indonesia and born in reformation era. The method used in this research is framing method by Robert N. Entman’s which consist of four steps identification : defining problem, diagnosing causes, moral judgement and a treatment recommendation. This research found that Kompas news covered the border dispute must be negotiated as recognition of Indonesia dignity.